2022
DOI: 10.3389/fped.2021.769937
|View full text |Cite
|
Sign up to set email alerts
|

A Diagnostic Model for Kawasaki Disease Based on Immune Cell Characterization From Blood Samples

Abstract: Background: Kawasaki disease (KD) is the leading cause of acquired heart disease in children. However, distinguishing KD from febrile infections early in the disease course remains difficult. Our goal was to estimate the immune cell composition in KD patients and febrile controls (FC), and to develop a tool for KD diagnosis.Methods: We used a machine-learning algorithm, CIBERSORT, to estimate the proportions of 22 immune cell types based on blood samples from children with KD and FC. Using these immune cell co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Disturbed immune response is one of the important pathogenetic mechanisms of KD, in which monocytes and their molecular markers can be used as diagnostic indicators of KD (20). Eight immune cells, including monocytes, construct a diagnostic scoring system that can be used to differentiate KD from febrile infections (21). All of the above studies suggested that monocytes are a risk factor for KD, but our study shows the opposite result.…”
Section: Discussionmentioning
confidence: 52%
“…Disturbed immune response is one of the important pathogenetic mechanisms of KD, in which monocytes and their molecular markers can be used as diagnostic indicators of KD (20). Eight immune cells, including monocytes, construct a diagnostic scoring system that can be used to differentiate KD from febrile infections (21). All of the above studies suggested that monocytes are a risk factor for KD, but our study shows the opposite result.…”
Section: Discussionmentioning
confidence: 52%